Review of neoplastic cases of domestic mammals diagnosed at Universiti Pertanian Malaysia (1979-1984) - Chooi, Kum Fai (Persatuan Doktor Veterinar Malaysia, 1985)
The prevalence of neoplasia in the canine, feline, equine, bovine, ovine, caprine and porcine species was studied. The incidence of neoplasms was highest in canines, comprising 9.2% of 459 cases examined. In this species 19 histological types of tumours were diagnosed, with transmissible venereal tumours as the most common. Few neoplasms were observed in the porcine, caprine, bovine and ovine species. There were no tumours recorded in felines and equines.